Is the Role of Circulating in an OR within the Scope of Practice for the RPN? - Christiansen, Kathi (Operating Room Nurses Association of Canada Journal, 2000)
The focus of care at St. Joseph’s Health Centre’s Operating Room is for Ambulatory, Short Stay patients. RPN’s and RN’s are part of the team providing patient care. Redesign upskilled the RPN at the London, Ontario Health Center to function in the Circulating Role. Role Clarity was underway at SJHC. The purpose of Role Clarity was to guide units within the Health Center in choosing the appropriate assignment for RNs, RPNs, and Attendants. The Operating Room Practice Council systematically and respectfully problem solved the question: Is the role of circulating in an Operating Room within the scope of practice for the RPN?